France : Financial Sector Assessment Program-Technical Note on Crisis Management and Bank Resolution Framework. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2013)
This technical note discusses key findings of the assessment of Crisis Management and Bank Resolution Framework for France. The findings reveal that the crisis preparation, crisis identification, and crisis management processes in the supervisory authority (ACP) are comprehensive and well structured. Without having a formal U.S.-type 'PCA-regulation,' the ACP identifies weak banks and requests appropriate remedial measures to be taken. The ACP also actively uses the Basel II Pillar 2 instrument to require add-ons on an individual-bank basis to the minimum regulatory capital requirements, reflecting the assessed riskiness of a bank.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet